The role of active ingredients nanopowder Stichopus hermanii gel to bone resorption in tension area of orthodontic tooth movement - Noengki Prameswari; Arya Brahmanta (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: Orthodontic tooth movement is a continual and balanced process between bone deposition and bone resorption in pressure and tension sites. Stichopus hermanii is one of the best fishery commodities in Indonesia. It is natural and contains various active ingredients such as hyaluronic acid, chondroitin sulphate, cell growth factor, eicosa pentaenoic acid (EPA) docosa hexaenoic acid (DHA) and flavonoid that potentially play a role in orthodontic tooth movement. Purpose: The aim of this study was to investigate the active ingredients of nanopowder Stichopus hermanii promoting bone resorption in tension area orthodontic tooth movement. Methods: A quantitative test for active ingredients of stichopus hermanii was conducted. Thirty two male Cavia cobaya were divisibled became four groups. K (–) groups as a negative control group (without treatment), K (+) groups as a positive control group which were provided with a separator rubber for orthodontic tooth movement, and P1, P2 groups, which were treated with 3% and 3.5% stichopus hermanii for orthodontic tooth movement. After treatment the cavia cobaya were sacrificed. TRAP-6 expression as a osteoclast marker was examined by means of an immunohistochemistry method. Results: A one-way Anova test confirmed that TRAP-6 expression was significantly increased with p = 0.00 (p≤0,05) in P2 compared to K (+). P2 to K (–), P2 to P1 and P1 to K (+) had no significant differences Conclusion: Nanopowder Stichopus hermanii 3.5% has an active ingredient that could increase osteoclast activity to resorb periodontal ligament and alveolar bone in tension areas of orthodontic tooth movement.